Aggregates of fluorescent gels assembled by interfacial dynamic bonds. Issue 2 (19th October 2022) - Hu, Ziqing; Xu, Shaoyu; Zhang, Hanwei; Ji, Xiaofan
Abstract: Life, defined as the specific form of substance, is an integration of aggregates at various scales, ranging from single molecules to tissues. However, these building blocks of common aggregates are usually recognized as confining at the microscopic level, while there are few studies focusing on macroscopic building blocks for aggregates. Fluorescent gels, as the important macroscopic building blocks, are drawing researchers' attention on account of their extraordinary fluorescence as well as soft material properties. Inspired by nature, fluorescent gels can be aggregated through interfacial adhesion. According to the driving forces for interfacial adhesion, a series of aggregates of fluorescent gels (AFGs ) was summarized, including H‐bond, metal coordinations, host‐guest interactions, hydrophobic interactions, electrostatic interactions, dynamic covalent bonds as well as multiple driving forces. These AFGs own dynamic assembled behaviors and rich stimuli responsiveness, which could be applied to information storage, sensing, biomedical systems, and so on. The authors anticipate this review can accelerate the development of aggregate science, especially based on macroscopic building blocks. Abstract : As an important kind of macroscopic building blocks, fluorescent gels could be assembled to form aggregates by using dynamic bonds, showing a diversity of fluorescent colors.